Answer:
[tex]\large\boxed{\left(\dfrac{f}{g}\right)(8)=-169}[/tex]
Step-by-step explanation:
[tex]\left(\dfrac{f}{g}\right)(x)=\dfrac{f(x)}{g(x)}\\\\f(x)=3-2x,\ g(x)=\dfrac{1}{x+5}\\\\\text{Substitute:}\\\\\left(\dfrac{f}{g}\right)(x)=\dfrac{3-2x}{\frac{1}{x+5}}=(3-2x)\left(\dfrac{x+5}{1}\right)=(3-2x)(x+5)\\\\\left(\dfrac{f}{g}\right)(8)\to\text{put x = 8 to the equation of a function}\ \left(\dfrac{f}{g}\right)(x):\\\\\left(\dfrac{f}{g}\right)(8)=(3-2\cdot8)(8+5)=(3-16)(13)=(-13)(13)=-169[/tex]